(untitled) (Anclajes, 2019)
the work of Juan José Saer highlights the mediated nature of language through the verification of the unavoidable presence of a gaze. However, the detailed description of the characters’ perception in his novels presents a problem that transcends that recognition. For in his narrations the gaze faces obstacles that hinder its projection, summoning a question. In this paper we study the dimensions of this caesura figure as a privileged space of inquiry about the subject of the gaze. Based on the follow-up of a series of textual operations included mainly in El limonero real (1974) and in Nadie nada nunca (1980), in which the reading process is subverted to its basic assumptions, we recognize the ambivalent “half-erased” status of meaning in the literary text between understanding attempts and their denial.